MENINGKATKAN SOSIAL EMOSIONAL ANAK PADA KELOMPOK B MELALUI PERMAINAN TRADISIONAL BAKIAK DI TK AT-TAQWA KEJAWAN GRUJUGAN BONDOWOSO - Halimatus Sakdiyah (Atthufulah : Jurnal Pendidikan Anak Usia Dini, 2020)
The purpose of this study was to determine the implementation and results of traditional clogs game activities to improve children's emotional social abilities in group B at At-Taqwa Kejawan Grujugan in Bondowoso. Researcher used the Classroom Action Research (CAR) approach with research subjects in group B Tk At –Taqwa Kejawan Grujugan Bondowoso. This research was conducted in two cycles and the results showed that there was an increase in children's emotional social through traditional clogs,that before the action 19%, cycle I reached 62%, cycle II reached 81%. The conclusion of this research is that through traditional clogs games can improve the emotional social of B group children at Tk At –Taqwa Kejawan Grujugan Bondowoso.